Analysis of Tax Policy Strategies Related to Dividend Tax in an Effort to Increase Investors at the Primary Tax Office of Menteng Dua, Jakarta - Dwi Agustina; Yosua Richard Angky; Johansyah Zaini (Yayasan Ilomata, 2022)
The government issued Government Regulation Number 9 of 2021 to improve the investment climate and accelerate economic recovery in Indonesia. One of the policies passed was a dividend tax. This study aims to analyze the policy strategy carried out by the Primary Tax Office of Menteng Dua, Jakarta to increase the number of investors by utilizing the dividend tax that has been made by the government. Data collection in this study was conducted through literature study, interviews, observation, and documentation. The results of the analysis show that the dividend tax policy strategy carried out by the Primary Tax Office of Menteng Dua, Jakarta to increase the number of investors was to develop a culture that supports the strategy, create an effective organizational structure, direct marketing efforts policies, plan budgets, develop and empower information systems, and connect the employee and organizational performance. Although several strategies had been implemented, the implementation had not been optimal because due to the large number of taxpayers the tax office did not conduct a special campaign regarding dividend tax. The campaigns were carried out only through representative accounts without a special budget.